Pengembangan Keterampilan Berpikir Kritis dalam Pembelajaran Fiqih di Madrasah Ibtida’iyah - Khotimah, Kusnul; Junanto, Subar (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
The purpose of this study is to examine developing critical thinking skills in learning fiqh of MIN 7 Boyolali, as well as the supporting and inhibiting factors. This research uses a qualitative method with a case study approach. Data collection techniques using interviews, observation, and documentation. Data analysis techniques are data collection, data reduction, and conclusion drawing/verification. The results showed that developing critical thinking skills in fiqh learning at MIN 7 Boyolali has been carried out quite well. This shows that the fiqh teacher at MIN 7 Boyolali has a good understanding of critical thinking skills and how to apply them in fiqh learning. In addition, teachers have also used various learning methods that can develop critical thinking skills. However, there are still some things that can be improved in developing critical thinking skills in fiqh learning at MIN 7 Boyolali, namely teachers need to provide more opportunities for students to practice critical thinking, and the fiqh curriculum and syllabus need to be reviewed to place more emphasis on developing critical thinking skills. The contribution of this research is to provide an overview of the development of critical thinking skills in fiqh learning at MIN 7 Boyolali and provide recommendations to improve the development of critical thinking skills.